Gentrification process of a degraded space turned into a cultural showcase. The case of the Historic Center of Malaga - Castro-Noblejas, Hugo; Sortino-Barrionuevo, Juan Francisco; Reyes-Corredera, Sergio (Revista de Estudios Andaluces, 2022)
The Historic Center of Malaga has been undergoing a series of profound architectural, functional and social transformations in recent decades. These processes have not yet been systematically analysed, despite the fact that the study of urban processes such as gentrification is a very present field of academic research. This work aims to determine if the Historic Center of Malaga has presented a gentrification process from the last third of the 20th century to the beginning of the 21st century. The results were obtained and analysed on the basis of a selection of demographic, socio-economic and property indicators that facilitate the identification of this urban phenomenon. The results obtained indicate the existence of an advanced gentrification process. This study establishes the basis for a broader avenue of investigation of this Malaga urban space.